Polish Rheumatologists and Rheumatoid Arthritis Patients Differ in Their Opinions About Treatment Inefficacy - Anna RACZKIEWICZ; Aleksandra JUSZKIEWICZ; Malgorzata TLUSTOCHOWICZ; Witold TLUSTOCHOWICZ (Archives of Rheumatology, 2015)
Objectives: This study aims to detect the differences of opinion between rheumatoid arthritis patients and rheumatologists concerning factors affecting escalation of disease modifying antirheumatic drugs (DMARDs). Materials and methods: The study included 82 rheumatoid arthritis patients (14 males, 68 females; mean age 61.4±11 years; range 35 to 84 years) and 85 rheumatologists (26 males, 59 females; mean age 49.7±11.7 years; range 33 to 77 years). All participants were asked to complete a survey which was composed of nine factors related to the ineffectiveness of RA treatment and the necessity of treatment change or DMARDs escalation. The patients were also asked to assess their satisfaction with current treatment and trust in their doctor. We collected demographic data of patients as well as their Disease Activity Score 28, erythrocyte sedimentation rate, and Health Assessment Questionnaire score. Results: Of the patients, 83% declared confidence in their doctor and 74.5% declared satisfaction with current therapy, while only 44% achieved low disease activity. The most important reasons for patients to escalate their therapy were persistent pain, functional impairment, progression of erosions, and rheumatologist’s decision. For rheumatologists, the most important issues were progression of erosions, joints’ swelling, high erythrocyte sedimentation rate, and morning stiffness. Radiological progression, joints’ swelling, and high erythrocyte sedimentation rate were considered more important for DMARD escalation by physicians than by patients. Middle-aged rheumatologists of 41-60 years of age and female rheumatologists were more inclined to consider patients’ opinion as a factor for treatment change. Conclusion: Different factors are important for rheumatologists and rheumatoid arthritis patients regarding DMARDs escalation. Treatment satisfaction is determined not only by disease activity indices but also by other patient-oriented factors. Improved communication between patients and physicians plays a significant role in achieving the therapeutic goal of tight control of the disease.